Is Cupping Therapy in Combination with Routine Physical Therapy Effective in the Management of Knee Osteoarthritis? A Randomized Controlled Trial - Sara Abolahrari-Shirazi; Farahnaz Ghafari Nezhad; Ziba Ahmadpour; Leila Zare; Farahnaz Emami (Shiraz University of Medical Sciences, 2018)
Background: Osteoarthritis is a common form of arthritis accompanied by varying degrees of disability and reduced quality of life. Several management regimens are available to treat knee osteoarthritis. Cupping therapy is used to treat musculoskeletal disorders but its effects on knee osteoarthritis has remained unclear. The study aimed to compare the effectiveness of intermittent cupping therapy plus routine physical therapy with routine physical therapy alone in patients with knee osteoarthritis. Methods: Twenty-six patients with knee osteoarthritis were randomly assigned into two groups: intermittent cupping therapy plus routine physical therapy (intervention group, n=13) and routine physical therapy alone (control group, n=13). In the routine physical therapy group, transcutaneous electrical nerve stimulation, hot pack, and ultrasound were used, while in the cupping therapy group, intermittent vacuum therapy was used together with routine physical therapy. Both groups received 10 treatment sessions over a period of 2 weeks. Pain intensity was measured via visual analog scale (VAS). Further, functional disability was assessed using the Persian version of Western Ontario and McMaster Universities (WOMAC) osteoarthritis index questionnaire. Finally, knee joint passive range of motion (ROM) was measured with photography preand post-intervention. Results: At follow-up, both groups had significantly lower pain intensity and functional disability, and higher knee passive ROM compared to their respective pre-intervention values (P<0.05). However, no significant differences were observed between groups in pain intensity or passive ROM in the knee (P>0.05). Differences in total WOMAC scores between pre- and post-intervention were significantly greater in the control group than in the intervention group (P<0.05). Conclusion: Based on the results, both interventions can be effective in relieving symptoms in patients with knee OA.